Quantum corrections in thermodynamics of black holes modified by nonlinear electrodynamics and their observational signatures - Sucu, Erdem; Sakalli, Izzet; Pourhassan, Behnam (World Scientific Publ Co Pte Ltd, 2025)
This work explores the thermodynamic and observational properties of black holes (BHs) influenced by nonlinear electrodynamics (NED) while incorporating quantum corrections. We analyze modifications to BH thermodynamics due to NED effects, focusing on quantum-corrected entropy, Hawking temperature, and phase transitions. Our study introduces a new framework that integrates quark-antiquark confinement effects into the NED formalism, revealing substantial deviations in the thermodynamic stability of BHs. The interplay between EC entropy and classical Bekenstein-Hawking entropy is examined, leading to refined predictions for key thermodynamic quantities. Additionally, we investigate the observational signatures of NED BHs, including their shadows, quasinormal modes (QNMs), and gravitational redshift. By performing a photon sphere analysis, we compute the modifications in BH shadows and identify potential observational markers linked to NED effects. Moreover, we derive the QNMs of these BHs, shedding light on their stability and dynamical behavior under scalar perturbations. Gravitational redshift calculations further illustrate how NED alters the spectral properties of emitted radiation near BHs, presenting new possibilities for testing these effects through astronomical observations.
Keywords: Black hole; thermodynamics; gravitational lensing; nonlinear electrodynamics; shadow; quasinormal modes; redshift; quark; quantum corrections